The Phytopharmaceutical Development Of Eurycoma Longifolia Jack And Its Mechanistic Studies On Rat Spermatogenesis - Low, Bin Seng (2013)
Eurycoma longifolia Jack is popularly used as a traditional medicine for various pharmacological properties including the improvement of sexual and male fertility. From a previous study, the bioactive methanol extract of E. longifolia was fractionated through resin-packed column chromatography and yielded four fractions. The fraction 2 (F2) significantly increased the spermatogenesis of rats. High performance liquid chromatography (HPLC) analysis revealed that the bioactive fraction F2 contained 32.1 % (w/w) of total major quassinoids comprising 14.5 % (w/w) of eurycomanone. The male rats orally administered with 25 mg/kg of F2 and 250 mg/kg of E. longifolia aqueous extract that contained almost similar in concentration of eurycomanone, significantly increased the sperm concentration when compared with that of the control animals. Upon oral administration of F2 for 52 days, male rats showed an improvement of the spermatogenesis. The increase of the sperm concentration upon treatment with F2 was further confirmed by the microscopic morphometrical studies showing that the population of the germ cells, spermatozoa production rate, the height of germinal epithelium and Leydig cells count was significantly elevated. The administration of F2 increased the levels of testosterone, luteinizing hormone, follicle stimulating hormone but reduced the estrogen level in plasma, further indicates the effect of E. longifolia on the hypothalamic-pituitary-gonadal axis. In vitro study showed that eurycomanone, the major quassinoid, significantly increased the testosterone production in the isolated rat testis interstitial cells. The increase in testosterone and decrease in estrogen induced by eurycomanone in vitro were consistent with the in vivo study.